The use of role playing as an interactive technique for improving the speaking skill in learning english as a foreign language among 3rd year students at centro educativo integral Alborada, during the academic period 2013-2014 - Bustan Japon, Mariana del Cisne (2015)
This action research study was focused on the improvement of the speaking skill with the use of role playing technique among third year students at Centro Educativo Integral “Alborada”. An intervention plan with eight sessions was carried out to improve the skill. Researchers’ made tests and questionnaires were designed and used to measure the five students´ progress and perception about the use of role playing. Field diary sheets were also used every session to see the students’ growth. The results indicated that role playing facilitated meaningfully the improvement of the speaking which was reflected in the remarkable growth of the posttest scores and students’ progress during the intervention. The answers received from the questionnaires also confirmed the students’ perception about the use of role playing to master speaking. It is concluded that this study helped the students to improve their speaking skill and the researcher to practice her teaching skills.